The Effect of 0.5% Sodium Tetradecyl Sulfate on a Venous Lake Lesion - Jung, Suck Joon (Ann Dermatol, 2008)
BACKGROUND: A venous lake lesion is a venous ectasia that occurs on the exposed skin of elderly people. Although a number of therapies such as surgical excision, laser therapy, infrared coagulation, cryotherapy and sclerotherapy have been used to treat venous lakes, there is no guideline for treating this lesion. OBJECTIVE: The purpose of this study was to determine whether 0.5% sodium tetradecyl sulfate (STS) is effective for the treatment of venous lake lesions. METHODS: Twelve patients with venous lake lesions were enrolled In this study. After proper antiseptic preparation, 0.5% STS was slowly injected into each subject's lesion, and this was followed by immediate compression for 10 minutes. RESULTS: After treatment, all of the patients' lesions cleared completely. The average number of treatments was 2.15±1.28. Two patients experienced mild side effects such as light pain and paresthesia, and these soon disappeared. There were no serious side effects reported during treatment. The mean follow up period was 29.58±13.48 months. CONCLUSION: We have demonstrated that sclerotherapy with 0.5% STS was quite effective for treating venous lake lesions, and this treatment caused no serious adverse effects.